Desvendando as sequências de Fibonacci, Lucas e Gibonacci - Fonseca, Luciana da (2023)
The Fibonacci sequence is considered one of the most beautiful and perfect sequences in mathematics. Considering this fact, we present a study regarding the Fibonacci sequence and its occurrences. Initially, we elucidate a brief history of Fibonacci and its sequence. Right away we approach the definition of the Fibonacci, Lucas and Gibonacci sequences and, some of the identities that relate these sequences. We also exhibit several occurrences associated with these sequences, where some of them were developed using Geogebra software. Finally, we propose some activities that can be applied in elementary school where we seek to emphasize a distinguished approach using math games, problem solving, and information technology.